Calculation of the Spontaneous Polarization and the Dielectric Constant for the Ferroelectric N(CH3)4HSO4 Using the Mean Field Model - Yurtseven H.; Celik M.; Karacali H. (High Temperature Materials and Processes, 2017)
The temperature dependences of the spontaneous polarization and the dielectric constant (susceptibility) are calculated using the mean field model for the ferroelectric N(CH3)4HSO4. Expressions derived from the mean field model for the spontaneous polarization and the inverse susceptibility are fitted to the experimental data from the literature. The fitting parameters in the expansion of the free energy in terms of the spontaneous polarization are determined within the temperature intervals in the ferroelectric and paraelectric phases of N(CH3)4HSO4. Our results show that the temperature dependences of the spontaneous polarization and the dielectric constant as predicted from our mean field model, describe adequately the observed behavior of N(CH3)4HSO4 in the ferroelectric and paraelectric phases.